2006
DOI: 10.1111/j.1469-7998.2006.00144.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction of the mobile descended larynx during groaning enables fallow bucks (Dama dama) to lower their formant frequencies

Abstract: A permanently descended larynx is found in humans and several other species of mammals. In addition to this, the larynx of species such as fallow deer is mobile and in males it can be retracted during vocalization. The most likely explanation for the lowered retractable larynx in mammals is that it serves to exaggerate perceived body size (size exaggeration hypothesis) by decreasing the formant frequencies of calls. In this study, we quantified for the first time the elongation of the vocal tract in fallow buc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 28 publications
3
106
1
1
Order By: Relevance
“…Formants drop at the beginning of the bugle and reach a minimum plateau, characteristic of the vocal tract extension already identified in red deer stags and fallow deer bucks (McElligott et al, 2006), and consistent with the laryngeal movements observed in the videos of bugling male wapitis. Analysis of the formants from the recorded vocalisations indicates that the minimum formant spacing averages 222±7.8 Hz (mean± s.d.…”
Section: Formant Frequenciessupporting
confidence: 50%
“…Formants drop at the beginning of the bugle and reach a minimum plateau, characteristic of the vocal tract extension already identified in red deer stags and fallow deer bucks (McElligott et al, 2006), and consistent with the laryngeal movements observed in the videos of bugling male wapitis. Analysis of the formants from the recorded vocalisations indicates that the minimum formant spacing averages 222±7.8 Hz (mean± s.d.…”
Section: Formant Frequenciessupporting
confidence: 50%
“…Indeed, the 'size exaggeration' hypothesis (Ohala, 1984;Fitch, 1997;Fitch, 2002;Fitch, 2010) has been proposed to justify the permanently descended larynges found in other mammals (Fitch and Reby, 2001;Weissengruber et al, 2002;Frey and Gebler, 2003;Frey et al, 2011) and the elongated trachea present in some bird species (Fitch, 1999). More generally, the observation that several male mammals actively lower formants in their sexual calls (Fitch and Reby, 2001;Frey and Gebler, 2003;McElligott et al, 2006;Frey et al, 2007;Sanvito et al, 2007;Frey et al, 2011) suggests that selection for adaptations to exaggerate (or maximise) the acoustic impression of body size in reproductive contexts could be widespread in non-human animals (see Fitch and Hauser, 2002). Whether this is predominantly for deterring rivals and/or attracting females remains a key question for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a dissociation between female skull and body size appears to render formants poor cues to size in female giant pandas (Charlton et al, 2009), and may provide the causal basis for similar findings in other female mammals (Rendall et al, 2005;Pfefferle and Fischer, 2006). Furthermore, the presence of anatomical adaptations that allow callers to elongate their vocal tracts and lower formants (by lengthening the supra-laryngeal or nasal vocal tract) (Fitch and Reby, 2001;Frey and Gebler, 2003;McElligott et al, 2006;Frey et al, 2007;Sanvito et al, 2007;Frey et al, 2011) could also make formants unreliable cues to body size, unless physiological constraints can act as a barrier to further formant lowering (Fitch and Reby, 2001;Reby and McComb, 2003). Consequently, it cannot be assumed a priori that formants will provide reliable information on body size in a given species and, hence, it remains important to determine whether they do and, more generally, to test the prediction that formants are reliable cues to body size in a wider range of taxa.…”
Section: Introductionmentioning
confidence: 99%
“…This facial expression is made by protruding the lips, which effectively lengthens the vocal tract, and would generate the impression of a larger body size during vocalization [Ohala, 1984]. Similar to that for the visual size projection, the selection pressure for acoustic size projection is strong enough for many animals to develop permanently or mobilely lengthened vocal tracts [red deer Cervus elaphus: Fitch and Reby, 2001; fallow bucks Dama dama: McElligott et al, 2006; bird of paradise Phonygammus: Clench, 1978, and 60 bird species : Fitch, 1999]. Further evidence that such lengthening of the vocal tract is for the sake of exaggerating body size is the fact that it is often found only in male animals, which suggests its importance for mating competition [Fitch, 1994;Ohala, 1984].…”
Section: Introductionmentioning
confidence: 99%